Pengembangan Wisata Watu Gendong Melalui Optimalisasi Manajemen dan Promosi Digital di Desa Beji Kabupaten Gunung Kidul - Bintang Wicaksono; Murniady Muchran; Anindita Imam Basri (Jurnal Pengabdian UNDIKMA, 2023)
This community service was carried out with the aim of developing Watu Gendong tourism in Beji Village. Watu Gendong is a tourist attraction that has the potential to be developed into a local and national tourist destination. The implementation of the Watu Gendong tourism development was carried out in Beji Village, Ngawen District, Gunungkidul Regency. This activity is carried out using the training method. The results of this dedication include increasing the Partner's ability to manage Watu Gendong tourism, the management structure of Watu Gendong tourism, and digital promotional facilities in the form of websites and sosial media. With good tourism management and digital promotion facilities that have begun to be built, it is hoped that Watu Gendong tourism will develop into a globally recognized tourist destination.